Energy position of maxima in response functions of ²H nucleus with q = 1 - 1,5 fm⁻¹ - Buki, A.Yu.; Shevchenko, N.G.; Nenko, I.A.; Khomich, A.A.; Pashchuk, S.A.; Evseev, I.G. (Вопросы атомной науки и техники, 2000)
The problem of measuring a quasielastic electron scattering peak energy on nuclei is discussed.